INCREASED RELIGIOUS AND MORAL VALUES OF CHILDREN AGED 4-5 YEARS THROUGH ROLE-PLAYING METHODS IN ALHIJRAH KINDERGARTEN TOMPOBALANG GOWA DISTRICT - Egi Mawarni; Riskal Fitri; Sadaruddin (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The purpose of this study was to increase religious and moral values ​​through the role playing method for children aged 4-5 years at Alhijrah Tompopalang Kindergarten. The method used is a descriptive quantitative approach and this type of research is classroom action research (CAR), which consists of two cycles where each cycle is held in two meetings. The focus of this research is to increase religious and moral values ​​in children aged 4-5 years at Alhijrah Tompobalang Kindergarten. The results of the research after applying the role-playing learning method using fruits were carried out repeatedly in cycle I, meeting I and meeting II, very good child development (BSB) reached 51.11% and meeting II reached 55.55% and at cycle II meeting I and meeting II child development reached 62.22% and meeting II reached 84.44%. From these results it can be concluded that the use of role playing methods can increase religious and moral values ​​in children aged 4-5 years.